Chinese OFDI in Africa: trends, prospects, threats? - Allard, Gayle (Henry Stewart Talks, 2013)
Chinese FDI in Africa, Emerging MNEs, Chinese FDI vs global FDI, Chinese FDI and African corruption, Chinese FDI and mineral exporters, Conclusions, Western policy implications